A Sociocultural Perspective: Seeking Evidence of Development in a PACE Approach to Grammar Instruction. Issue 1 (26th October 2021) - Davin, Kristin J.; Kushki, Ali
Abstract: Situated within Sociocultural theory (SCT), this article analyzed an existing data set (Toth, 2021a, 2021b, 2021c, available at https://www.iris-database.org ) to investigate learners' development through participation in a dialogic approach to grammar instruction called PACE. The target of instruction was the Spanish pronominal clitic se . Microgenetic analysis of the interaction between the teacher and learners was used to track two students' development during both small‐group work and whole‐class instruction. To analyze the process of development, evidence of obuchenie (i.e., teaching‐learning activity) that preceded changes in each learner's performance was sought. These findings were compared to the two students' performance on a pre‐, post‐ and delayed‐intervention picture description task. Findings highlight the instances of mediation that promoted students' metalinguistic awareness and use of se . The article concludes with a discussion of the extent to which claims of development could be made based on the provided data set and considerations of the affordances of dialogic versus deductive explanations of grammar. Abstract :